Psycholinguistic features of creative literary translation - Dyachuk, Nataliya (Lesya Ukrainka Eastern European National University, 2014)
The paper outlines the study of translation from the point of view of creativity. The research generalizes and empirically verifies a psycholinguistic approach to the study of creativity in the translation of fiction. A psycholinguistic model of literary translation made it possible to define some avenues of empirical research into future literary translators’ creative strategies. Individual creativity is viewed as the main indicator of future literary translators’ creative potential. The Smile by R. Bradbury and its Ukrainian versions made both by professional translators Lada Kolomiyets, Andriy Yevsa, Yaroslav Vepryniak, and 183 novice translators, were the principal sources of the analysis. As a result of studying the translating strategies applied, three groups of novice translators were defined – ‘combining strategy group’, ‘analogical strategy group’, and ‘reconstructing strategy group’. The novice translators’ versions manifested poor and sufficient levels of individual creativity, as they tended to apply only the simplest translating techniques, such as addition and deletion, rarely antonymous translation as the most creative translation solution. By contrast, mature translators used creative reconstructing and universal strategies, as they applied a variety of translating transformations including generalization, specification, addition, deletion, integration, full rearrangement, and antonymous translation. The empirical research results based on three of Cattell’s personality factors showed high correlation indices between translators’ personality traits and their literary translation creativity.
Keywords: literary translation; creativity; translation strategies; translating transformations; personality traits